Sertoli-Leydig Cell Tumour and DICER1 Mutation: A Case Report and Review of the Literature - B. Wormald; S. Elorbany; H. Hanson; J. W. Williams; S. Heenan; D. P. J. Barton (Case Reports in Obstetrics and Gynecology)
Sertoli-Leydig cell tumours of the ovary (SLCT) are rare tumours predominantly caused by mutations in the DICER1 gene. We present a patient with a unilateral SLCT who had an underlying germline DICER1 gene mutation. We discuss the underlying pathology, risks, and screening opportunities available to those with a mutation in this gene as SLCT is only one of a multitude of other tumours encompassing DICER1 syndrome. The condition is inherited in an autosomal dominant fashion. As such, genetic counselling is a key component of the management of women with SLCT.